African American Maternal Power and the Racial Socialization of Preschool Children. - Edwards, Adrienne; Few-Demo, April (Sex Roles, 2016)
In the present qualitative study, we applied an integrated Black feminist-child development theoretical framework to examine how 12 African American mothers engaged the racial socialization process with their preschool-age girls and boys in the U.S. state of South Carolina. We specifically examined (a) the strategies and messages that mothers use during the racial socialization process and (b) mothers' perceptions of external sources that influenced their children's racial socialization experiences. Two major themes emerged from data analyses: Motherwork as Conscientization and Doing African American Mothering. An overarching finding was that mothers found the racial socialization of their children to be characterized by a struggle to maintain control over racialized messaging received by their children and a feeling of powerlessness over the influence of external forces in racial socialization. Mothers preferred to use cultural socialization and egalitarian socialization with their young children and believed that there was a developmental time of readiness for having conversations involving race and race discrimination.